The influence of big data and artificial intelligence tools in marketing 4.0 (Research, Society and Development, 2021)
The suitability of artificial intelligence and big data in marketing 4.0 made the approach to marketing innovative, contributing to increased sales, competitive advantage, increased ROI, process optimization, advanced customization for customers and delivering innovative experiences for customers. The objective of the study was to present information about the fourth industrial revolution, the impact of big data on business, artificial intelligence and its subfields and, finally, marketing 4.0. In this qualitative review, the articles were selected from the Scielo and Google Scholar databases, and books were also selected for the development of the work. As a final result, emphasis was placed on how artificial intelligence and big data tools revolutionized marketing.